2006
DOI: 10.1007/s11102-006-9277-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor-regulated tyrosine kinase substrate (HGS) and guanylate kinase 1 (GUK1) are differentially expressed in GH-secreting adenomas

Abstract: Pituitary tumors, adenomas in their vast majority, represent around 10-15% of the intracranial neoplasms. Pituitary carcinomas are exceedingly rare. Clinically, these neoplasms cause hormonal dysfunctions, and mass effect symptoms as headache and visual disorders in the case of macroadenomas. Pituitary tumorigenesis is still poorly understood. In order to investigate the expression of cancer-related genes in pituitary tumors, we employed a human cancer cDNA macroarray membrane with 1176 well-characterized huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…This finding may be consistent with a former report indicating that Hrs is highly expressed in growth hormone-secreting adenoma (49). The spectra of Hrs expression seem to at least partially correlate with that of Wnt signal-related cancers, such as colorectal, gastric, and hepatocellular carcinomas (50).…”
Section: Discussionsupporting
confidence: 92%
“…This finding may be consistent with a former report indicating that Hrs is highly expressed in growth hormone-secreting adenoma (49). The spectra of Hrs expression seem to at least partially correlate with that of Wnt signal-related cancers, such as colorectal, gastric, and hepatocellular carcinomas (50).…”
Section: Discussionsupporting
confidence: 92%
“…HRS overexpression is known to be associated with malignancy and poor prognosis 5,46 , and previous studies shown an association of several types of human cancer, such as colorectal, gastric, and hepatocellular carcinomas, with a significantly elevated expression of HRS 47,48 , though the underlying related molecular mechanism remains unclear. Additionally, HRS-deficient mice, or mice with double knockout of STAM1 and STAM2 show embryonic mortality 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…De Rocha et al . found that GUK1 was differentially expressed in metastatic pituitary carcinoma 31 . Hu et al .…”
Section: Resultsmentioning
confidence: 96%